Abastecimento alimentar em contextos de crise: uma análise sobre o Haiti - John Osthe; Valdemar João Wesz Junior (Confins)
Historically and currently, the Republic of Haiti has faced multiple crises which have had an intense and direct impact on its population. This article aims to analyze the spaces, actors and dynamics of food supply in the country, focusing specifically on the small municipality of Saint-Raphaël (North Department). At the same time, emphasis will be placed on the role of madan sara, a central link in understanding food supply in Haiti. In addition to a literature review and analysis of secondary data, interviews were conducted with different stakeholders in Saint-Raphaël (farmers, consumers, retailers, madan sara, among others). The results show that the main place of supply in Saint-Raphaël is the municipal agricultural market, whose products are sold by both farmers and retailers. Both locally and nationally, a large part of the supply dynamic involves madan sara, independent individual women entrepreneurs who buy the produce of local farming families and take it to the bigger cities, bringing back other goods, especially imported products. They establish a vital connection between rural and urban areas, being key to the circulation of products and to Haiti's food supply, with an enormous capacity for resistance and resilience even in a national context marked by multiple crises.